Circulating Video Library. - The Museum of Modern Art, New York (New York : The Museum of Modern Art, 1983)
Acconci, Vito ; Alpert, Jon ; Ant Farm ; Ashley, Robert ; Atlas, Charles ; Beller, Claude ; Benglis, Lynda ; Bluckner, Barbara ; Blumberg, Skip ; Byrne, James ; Campbell, Colin ; Campus, Peter ; center, Downtown Community Television ; Cunningham, Merce ; D'Agostino, Peter ; DeFanti, Tom ; Emshwiller, Ed ; Fitzgerald, Kit ; Foreman, Richard ; Gorewitz, Shalom ; Hill, Gary ; Jonas, Joan ; Lord, Chip ; Michels, Doug ; Moore, Stefan ; Oursler, Tony ; Paik, Nam June ; Reeves, Dan ; Reilly, John ; Sanborn, John ; Sandin, dan ; Schreier, Curtis ; Serra, Richard ; Snyder, Bob ; Steina ; Tsuno, Keiko ; Vasulka, Steina ; Vasulka, Woody ; Veeder, Jane ; Velez, Edin ; Viola, Bill ; Wegman, William
Engels
boek